1987
DOI: 10.1152/ajprenal.1987.252.6.f1103
|View full text |Cite
|
Sign up to set email alerts
|

Quinidine effect on hydrosmotic response of collecting tubules to vasopressin and cAMP

Abstract: Quinidine, a compound thought to increase cytosolic calcium ion activity, has been found to inhibit the hydrosmotic response to vasopressin (VP) and adenosine 3',5'-cyclic monophosphate (cAMP) in the toad urinary bladder. To test whether this drug has a similar action in the mammalian nephron, the effect of quinidine on the hydraulic conductivity of the isolated perfused rabbit cortical collecting tubule (CCT) exposed to either 20 microU/ml VP or 10(-4) M 8-(p-chlorophenylthio) - adenosine 3',5' - cyclic monop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

1990
1990
2008
2008

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…Chloroquine is a weak base that increases pHi (31) that probably increases (Ca 2+ )i (28) to inhibit the increase in water permeability elicited by AVP or exogenous CAMP (30). Lorenzen, Frindt, Taylor and Windhager reported that quinidine induced elevation in (Ca 2+ )i suppressed AVP or CAMP stimulated water absorption in microperfused collecting tubules (30). This probably explains our previous observations of the absence of antidiuresis despite chloroquine-induced increases in plasma AVP concentrations (11).…”
Section: Discussionsupporting
confidence: 51%
“…Chloroquine is a weak base that increases pHi (31) that probably increases (Ca 2+ )i (28) to inhibit the increase in water permeability elicited by AVP or exogenous CAMP (30). Lorenzen, Frindt, Taylor and Windhager reported that quinidine induced elevation in (Ca 2+ )i suppressed AVP or CAMP stimulated water absorption in microperfused collecting tubules (30). This probably explains our previous observations of the absence of antidiuresis despite chloroquine-induced increases in plasma AVP concentrations (11).…”
Section: Discussionsupporting
confidence: 51%
“…Quin-Z acetoxymethyl ester, in concentrations higher than those typically used to measure cytosolic calcium concentration, is an effective buffer for intracellular calcium ions (217). When collecting tubules were treated with quin-2 acetoxymethyl ester and low bath [Cal, the inhibitory effect of quinidine on the actions of vasopressin and cAMP was prevented (134). These results strongly suggest that quin-Z acetoxymethyl ester exerts its protective effect by preventing the quinidine-induced rise in cytosolic free Ca 2 + concentration; furthermore, the quinidine-induced inhibition of the hydrosmotic response probably depends on a rise in cytosolic calcium.…”
Section: Effects Of Changes In Cytosolic Calcium On Renal Sodium Tranmentioning
confidence: 79%
“…In general, the conclusion has been that maneuvers thought to increase cytosolic free Ca 2 + concentration also inhibit the hydrosmotic response to both vasopressin and cAMP. Thus quinidine, a drug known to raise cytosolic Ca 2 + activity in proximal tubule cells of Necturus (135), inhibits vasopressin-and cAMP-induced water movement in toad urinary bladder (4,201,202,206) and mammalian collecting tubule (134). The calcium ionophares A23187 and X537A also inhibit the hydrosmotic response to vasopressin or cAMP in toad bladder (154).…”
Section: Effects Of Changes In Cytosolic Calcium On Renal Sodium Tranmentioning
confidence: 97%
See 2 more Smart Citations